Alif Ba Ta / Nor Suhaiza Md Khalid … [et al.] - Md Khalid, Nor Suhaiza; Mat Nurudin, Suzei; Mohd Zain, Zarina; Hishammudin, Nurul Nazirah (Division of Research and Industry Linkages, 2017)
Autism which also known as Autism Spectrum Disorder (ASD) is a development disorder of the brain that impairs the social and communication skills of both gender at young age. Hence the autism children required special items for them to engage in learning process specially when they reading. The autism Arabic alphabets book able to fulfilled the autism children requirement during their learning process in Islamic way. Most of the autism children wanted the books that have several features that are able to catch their interest during their learning proses however there are few book that able to meet the requirement and there is no specific book toward Islamic learning for the autism children. The objective of this book is to encourage the children with ASD to learn more about the Arabic alphabets because most the book more toward the basic alphabets, This book is to give the opportunity to the autism children to have a book that suitable to their interest and give the opportunity for them to learn the basic Arabic alphabets. The book is design with colorful that will catch the interest of the autism children to read and the book also unique in size where the size is in landscape view of half A4 paper that give the children the satisfaction when reading. This book is 2 in 1 features where the use of Velcro at each alphabets able to be used as an exercise to the children. The children able to read and do exercise by matching the alphabets also they able place the alphabets at the correct places. The use of Velcro able to attract the interest of autism kids where the texture of the Velcro itself. This book also incorporates the pop-out picture that able to catch the interest of the children. The book able to be promoted to the autism children and parents that want their children to learn Islam religion by started with the basic Arabic alphabets